SEROLOGICAL RESPONSE OF CHICKENS TO INFECTION WITH SALMONELLA-GALLINARUM S-PULLORUM DETECTED BY ENZYME-LINKED-IMMUNOSORBENT-ASSAY - Barrow, P. A.; Berchieri, A.; Alhaddad, O. (Amer Assoc Avian Pathologists, 1992)
The serological response to Salmonella pullorum and S. gallinarum infection in chickens was studied with an indirect enzyme-linked immunosorbent assay (ELISA). In broiler chickens, a more virulent strain of S. pullorum produced a significantly lower serum IgG titer than did a less virulent strain. In laying hens, the serum and egg-yolk IgG titers were very similar. In chickens infected with S. gallinarum, high IgG titers persisted for 30 weeks. In chickens reinfected with this strain, each reinfection was followed by transitory increases in IgG lasting no longer than 2 weeks. Serum samples from Brazil taken from a laying flock with evidence of fowl typhoid showed much higher antibody levels than did those from three uninfected flocks. Using lipopolysaccharide as the detecting antigen, infections caused by these salmonellae could be differentiated from those caused by other groups. Incorporation of the appropriate flagella antigen in the ELISA allowed differentiation between infections caused by S. pullorum and S. enteritidis.